Screening of Poly-β-hydroxybutyrate (PHB) Producing Bacteria and yeasts from locally vendored ‘Whey’ biowaste samples - Shishita Zahan Zisha; Tabassum Mumtaz; A.K.M Rashidul Alam (Biological Environment and Pollution, 2022)
Whey- a byproduct of the manufacture of cheese has several commercial uses. The present study was undertaken to explore the microbial load of the whey and the possible existence of biopolymer (PHB) producing microorganisms in this byproduct. Whey samples collected from different vendors in the locality of Mirpur, Dhaka were brought into laboratory and the microbial load was determined by serial dilution technique using nutrient agar and YEPD medium. From 30 colonies, 32 strains were preliminarily isolated. Out of 32 isolates, fifteen exhibited pink fluorescence on mineral medium, indicating the presence of PHB production inside cells. Among these, seven strains were identified as members of the genera Candida tropicalis; based on molecular characterization. The remaining 8 isolates were bacteria. It is interesting to note that, yeast isolates were obtained from locally vendored samples whereas bacterial strains were predominant in commercial samples. This work can be considered as the first step in the development of an ecofriendly bio-refinery pathway for cheese industry.